2017
DOI: 10.1371/journal.pone.0189981
|View full text |Cite
|
Sign up to set email alerts
|

Higher-than-expected prevalence of non-tuberculous mycobacteria in HIV setting in Botswana: Implications for diagnostic algorithms using Xpert MTB/RIF assay

Abstract: BackgroundNon-tuberculous mycobacteria (NTM) can cause pulmonary infection and disease especially among people living with HIV (PLHIV). PLHIV with NTM disease may clinically present with one of the four symptoms consistent with tuberculosis (TB). We describe the prevalence of NTM and Mycobacterium tuberculosis complex (MTBC) isolated among PLHIV who presented for HIV care and treatment.MethodsAll PLHIV patients presenting for HIV care and treatment services at 22 clinical sites in Botswana were offered screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…Although there have been suggestions that certain nontuberculous mycobacterial species (e.g. M malmoense ) may give false‐positive Xpert MTB/RIF results due to weak cross hybridization ( Agizew 2017 ), the false‐positive rate in specimens culture‐positive for NTM was similar to the overall frequency of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been suggestions that certain nontuberculous mycobacterial species (e.g. M malmoense ) may give false‐positive Xpert MTB/RIF results due to weak cross hybridization ( Agizew 2017 ), the false‐positive rate in specimens culture‐positive for NTM was similar to the overall frequency of false positives.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 15 Since the roll out of Xpert, studies in Botswana have shown that greater than half of positive sputum cultures among people living with HIV with a positive WHO symptom screen show non-tuberculous mycobacteria (NTM), demonstrating a significant limitation with reliance upon smear microscopy for diagnosis of TB, such as in our study. 17 Furthermore, our findings that TB was diagnosed no sooner with positive sputum smear raises concern for potential problems along the TB care cascade, such as laboratory delays, paucity of sputum sample collection, or clinician anchoring bias to CAP diagnosis.…”
Section: Discussionmentioning
confidence: 87%
“…In a study conducted by Shao, et al, (2015) [6] in China the prevalence of NTM was 3.37% among 1779 smear positive clinical isolates. However, reports from some sub-Saharan settings have been indicating that the prevalence of NTM among mycobacteria culture positive ranges from 4 to 9% [1]. Furthermore, a prospective study conducted in Nigeria reported that the prevalence of NTM among tuberculosis suspects was 15.5% [7].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted in Zambia and Botswana have shown an increase in females than males. According to them they suggested that the number could have been small in males because men delay in seeking care or un willing to seek care [1,10]. The ndings vary geographically due to different predisposing factors such as immune status, occupation and life style and possibly climatic conditions.…”
Section: Discussionmentioning
confidence: 99%